John Sibley correspondence - Sibley, John, 1757-1837.
ALS (Louisiana) from Sibley to an unnamed recipient providing an account of the Louisiana Territory at the time of cession. Includes extracts from Sibley's journals describing agriculture, commerce, inhabitants, settlements, and topography of New Orleans, La., and the surrounding region.
Physician, public official, and Indian agent from Louisiana.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Agriculture -- Louisiana; Cities and towns -- Louisiana; Louisiana -- Commerce; Louisiana -- Description and travel; Louisiana -- History -- 1803-1865.; Louisiana -- Social life and customs; New Orleans (La.) -- Description and travel; New Orleans (La.) -- History; Indian agents; Physicians; Public officials -- Louisiana